100 Differing opinions on clinical research between healthcare providers and lupus patients. (April 2019) - Arriens, Cristina; Forciea, Dylan; Carthen, Fredonna; McCance, Dallas; James, Judith A; Merrill, Joan T
Abstract : Background: Although systemic lupus erythematosus (SLE) disproportionately affects minority racial groups, they are significantly under-represented in clinical trials. This produces underpowered conclusions in race-based sub-group analyses. The decision to participate in clinical research is complex. Primary care providers (PCPs) have the ability to introduce the idea of clinical trials and to refer to specialists who participate in clinical trials. We evaluated SLE knowledge and implicit bias in clinical research participation in both PCPs and lupus patients. Methods: Lupus patients and PCPs completed a pre-test consisting of knowledge and belief questions followed by an educational program about lupus, clinical research, and human subjects protections. The same questions were repeated as part of the post-test. Responses to knowledge questions were analyzed by Fishers exact test for between group (patients vs. PCPs) comparisons or McNemars test for within group (pre-test vs. post-test) comparisons. Belief questions were scored on a Likert scale and analyzed by Mann-Whitney or Wilcoxon matched pairs for between group and within group comparisons. Results: 55 providers and 32 lupus patients completed the questionnaires and educational program. Knowledge topics included 1) triggers of SLE, 2) lupus racial differences, and 3) informed consent. There was a statistically significant difference between PCPs and patients on the pre-test informed consent topic (PCP 46% correct and patient 15%, p=0.0005). Post-test results were similar between groups. The education program resulted in improvement in knowledge scores for PCPs (Q1 42% to 85%, p<0.001; Q2 56% to 91%, p<0.0001; Q3 84% to 87%, p=0.5) and patients (Q1 38% to 84%, p=0.0003; Q2 56% to 75%, p=0.1; Q3 47% to 72% p=0.01). Topics of clinical trial belief questions included perceived risks of trials, differing racial background between provider and patient, education level needed for trial participation, and perceived effect of poverty on protocol compliance. The final topic demonstrated the greatest incongruence between PCPs and patients (figure 1 ). Conclusions: Beliefs about race, education, and poverty may impact referral to clinical trial centers and clinical trial participation. More than a third of PCPs believe that indigent people are poor candidates for clinical trials. Despite a shift away from this attitude following an educational program, providers remained much more likely than lupus patients to hold this opinion. Funding Source(s): HHS-OMH-CPI-MP-17-002-1